Maintenance of Transcription-Translation Coupling by Elongation Factor P - Sara Elgamal (American Society for Microbiology, 2016)
ABSTRACT Under conditions of tight coupling between translation and transcription, the ribosome enables synthesis of full-length mRNAs by preventing both formation of intrinsic terminator hairpins and loading of the transcription termination factor Rho. While previous studies have focused on transcription factors, we investigated the role of Escherichia coli elongation factor P (EF-P), an elongation factor required for efficient translation of mRNAs containing consecutive proline codons, in maintaining coupled translation and transcription. In the absence of EF-P, the presence of Rho utilization (rut) sites led to an ~30-fold decrease in translation of polyproline-encoding mRNAs. Coexpression of the Rho inhibitor Psu fully restored translation. EF-P was also shown to inhibit premature termination during synthesis and translation of mRNAs encoding intrinsic terminators. The effects of EF-P loss on expression of polyproline mRNAs were augmented by a substitution in RNA polymerase that accelerates transcription. Analyses of previously reported ribosome profiling and global proteomic data identified several candidate gene clusters where EF-P could act to prevent premature transcription termination. In vivo probing allowed detection of some predicted premature termination products in the absence of EF-P. Our findings support a model in which EF-P maintains coupling of translation and transcription by decreasing ribosome stalling at polyproline motifs. Other regulators that facilitate ribosome translocation through roadblocks to prevent premature transcription termination upon uncoupling remain to be identified. IMPORTANCE Bacterial mRNA and protein syntheses are often tightly coupled, with ribosomes binding newly synthesized Shine-Dalgarno sequences and then translating nascent mRNAs as they emerge from RNA polymerase. While previous studies have mainly focused on the roles of transcription factors, here we investigated whether translation factors can also play a role in maintaining coupling and preventing premature transcription termination. Using the polyproline synthesis enhancer elongation factor P, we found that rapid translation through potential stalling motifs is required to provide efficient coupling between ribosomes and RNA polymerase. These findings show that translation enhancers can play an important role in gene expression by preventing premature termination of transcription.